A mitochondrial targeted two-photon iridium(III) phosphorescent probe for selective detection of hypochlorite in live cells and in vivo. (June 2015) - Li, Guanying; Lin, Qian; Sun, Lingli; Feng, Changsheng; Zhang, Pingyu; Yu, Bole; Chen, Yu; Wen, Ya; Wang, Hui; Ji, Liangnian; Chao, Hui
Abstract: Endogenous hypochlorite ion (ClO − ) is a highly reactive oxygen species (ROS) that is produced from hydrogen peroxide and chloride ions catalyzed by myeloperoxidase (MPO). And mitochondrion is one of the major sources of ROS including ClO − . In the present work, a two-photon phosphorescent probe for ClO − in mitochondria was developed. An iridium(III) complex bearing a diaminomaleonitrile group as ClO − reactive moiety specifically responded to ClO − over other ions and ROSs. When the probe was reacted with ClO − to form an oxidized carboxylate product, a significant enhancement in phosphorescence intensity was observed under one-photon (402 nm) and two-photon (750 nm) excitation, with a two-photon absorption cross-section of 78.1 GM at 750 nm. More importantly, ICP-MS results and cellular images co-stained with Mito-tracker Green demonstrated that this probe possessed high specificity for mitochondria. This probe was applied in the one- and two-photon imaging of ClO − in vitro and in vivo. The results suggested endotoxin lipopolysaccharide (LPS) induced ClO − mostly generated in the liver of zebrafish.